EFEKTIVITAS SALEP EKSTRAK DAUN BAMBU, MENIRAN, BIJI PEPAYA SEBAGAI PENJINAK TUMOR DAN KANKER PAYUDARA - Wulandari, Silvi Fatika; Ningrum, Dwi Setya; Febriani, Mila (Jurnal Inovasi Daerah, 2023)
Bamboo plants are a source of flavonoids which are beneficial for the health of the body. To treat tumors and breast cancer, this study aims to make a synergistic ointment from the extracts of papaya seeds, meniran and bamboo leaves and a white vaseline base. Methods of data collection using experiments with accidental sampling method in the form of respondents who have had tumors and breast cancer. Data analysis used descriptive comparative analysis. Vaseline, papaya seed extract, meniran extract, and bamboo leaf extract form the composition of the bamboo leaf extract ointment. The bamboo leaf extraction process was carried out using a maceration strategy using 95% ethanol solvent. This cream-like ointment has a brown color, a pH of 6.5 and smells like bamboo leaf extract. The ointment has a spread of 3.5 cm and an adhesion time of 3.66 seconds. The content of flavonoids in the ointment was 0.1633% w/w QE and phenolics 0.371% w/w GAE. The content of cancer-preventing substances in salmon with 10 ppm is 10.09%. The ointment has an inhibitory effect on Gram-positive microorganisms of 9 mm, 10 mm and 11 mm. The results showed that there was a decrease in the size of breast tumors with a diameter of (3-5 cm) to (0.5-1 cm) with the treatment given 3 times a day for 124 days. Some respondents with stage IIA breast cancer experienced a reduction in pain and tender lumps with the treatment of giving ointment 3x a day for 17-37. The study concluded that an ointment containing meniran, papaya seeds, and bamboo leaf extract was effective against breast cancer and tumor tamer.